2017
DOI: 10.32890/jict2017.16.2.8233
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Serious Game Design Guidelines for Stimulating Cognitive Abilities of Children With Speech and Language Delay

Abstract: The creation of an effective therapeutic serious game (TSG) is highly dependent upon its design and the fundamental knowledge of the users. Furthermore, the TSG is designed for a purpose to the users by incorporating the needs of the users in all design components. Although numerous studies have been conducted on guidelines for designing serious games, to date, studies on the specific TSG’s design guidelines for stimulating the cognitive ability of children with speech and language delay (CSLD) has yet to be c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…The information in this guideline was obtained from relevant literature and interviews with speech pathologists. This guideline offers advice in 15 groups: “identification with the game, interface design, layout, demonstrations, reward/encouragement, performance feedback and guidance, personalization, adaptive games and challenges, social interaction, mobility, time management/restriction, repetition and rehearsal of skills, motivation and engagement, motor skill, and cognitive development.” 50 …”
Section: Discussionmentioning
confidence: 99%
“…The information in this guideline was obtained from relevant literature and interviews with speech pathologists. This guideline offers advice in 15 groups: “identification with the game, interface design, layout, demonstrations, reward/encouragement, performance feedback and guidance, personalization, adaptive games and challenges, social interaction, mobility, time management/restriction, repetition and rehearsal of skills, motivation and engagement, motor skill, and cognitive development.” 50 …”
Section: Discussionmentioning
confidence: 99%
“…Research has shown that serious games may have a myriad of positive effects on children experiencing DLDs and treatments (Ahmad Zaki et al, 2017;Elo et al, 2022). These observations are also extended to the therapeutic benefits associated with the use of board games and tabletop games in clinical settings (Noda et al, 2019).…”
Section: Existing Framework and Tools Towards Board Game Designmentioning
confidence: 98%